The Legal Protection for Doctors Regarding Medical Consent for Additional Medical Procedures - Made Agus Mahendra Inggas; Markoni Markoni; I Made Kantikha; Nardiman Nardiman (Green Publisher Indonesia, 2024)
Informed Consent is a prerequisite before a medical procedure can be considered legally valid and provide legal protection. Additional medical procedures can raise ethical, medical, and legal issues. There is no specific legislation focusing on legal protection for doctors regarding these additional medical procedures, but general principles of Indonesian law provide room for doctors to defend themselves if they have served patients professionally in accordance with professional standards and professional ethics. The research aims to analyze the procedures for obtaining consent for additional medical procedures and the legal protection for doctors providing these services to patients. The research method is conducted using a normative juridical approach with conceptual and case approach. The research results indicate that the purpose of obtaining consent for medical procedures is to protect patients from medical procedures performed without their knowledge and to provide legal protection for doctors from unforeseen and negative consequences. In the case of additional medical procedures, there must be renewed consent, and the procedure for obtaining consent depends on the availability of family members, either during or after the procedure. Doctors must comply with all medical standards and maintain complete medical records. In conclusion, the procedure for obtaining consent for additional medical procedures should be conducted during the procedure if family members are present or after the procedure if family members are absent, and legal protection for doctors in additional medical procedures is ensured through renewed written consent, maintaining complete medical records, and adhering to professional standards.